2012
DOI: 10.1007/s12565-012-0142-1
|View full text |Cite
|
Sign up to set email alerts
|

Location, number and morphology of parathyroid glands: results from a large anatomical series

Abstract: Surgical management of parathyroid gland disease may sometimes be difficult, due mainly to the surgeon's failure to successfully detect parathyroids in unusual locations. The records of 942 cadavers (574 men and 368 women) who underwent autopsy in the Department of Forensic Medicine in Athens during the period 1988-2009 were reviewed. In total, 3,796 parathyroid glands were resected and histologically verified. Parathyroid glands varied in number. In 47 cases (5 %), one supernumerary (fifth) parathyroid was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
0
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 18 publications
1
47
0
5
Order By: Relevance
“…Humans usually have four parathyroids; a large cadaveric study reported finding four in 93 %, five in 5 % and three in 2 % [3]. Embryologically, the parathyroid glands arise in the third and fourth pharyngeal arches before descending into the neck.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans usually have four parathyroids; a large cadaveric study reported finding four in 93 %, five in 5 % and three in 2 % [3]. Embryologically, the parathyroid glands arise in the third and fourth pharyngeal arches before descending into the neck.…”
Section: Introductionmentioning
confidence: 99%
“…Embryologically, the parathyroid glands arise in the third and fourth pharyngeal arches before descending into the neck. Their final position is variable, with 8.5 % located ectopically, 6.3 % in the mediastinum and 0.2 % within the thyroid tissue itself [3,4]. This variation makes identification challenging but experienced thyroid surgeons should be able to recognise and preserve the parathyroids in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…About 1% of the superior PT were located behind the junction of hypopharynx and upper esophagus. 10 The position of inferior PT is more variable. 42% were found on the anterior or lateral surfaces of the lower lobe of the thyroid, often hidden by vessels or creases in the thyroid.…”
Section: Resultsmentioning
confidence: 99%
“…The inferior PT are variable in location. 3 The blood supply of parathyroid are by ITA with some variable component from superior thyroid artery (STA). 4 To preserve the PT with intact blood supply, a medial to lateral dissection is advocated, with plane of dissection along the thyroid capsule.…”
Section: Introductionmentioning
confidence: 99%
“…1 The use of medication and biochemical tests is increased by postoperative hypoparathyroidism and hospital stay is prolonged thus adding to the overall cost of thyroidectomy. 2,3,4 The key to minimizing hypoparathyroidism following thyroidectomy is preserving the parathyroid gland and its blood supply. However, the relationship between the hypoparathyroidism and the number of parathyroid glands preserved is not well understood.…”
Section: Introductionmentioning
confidence: 99%